2003
DOI: 10.1098/rspb.2003.2493
|View full text |Cite
|
Sign up to set email alerts
|

Temporal analysis of archived samples indicates marked genetic changes in declining North Sea cod (Gadus morhua)

Abstract: Despite increasing evidence that current exploitation rates can contribute to shifts in life-history traits and the collapse of marine fish stocks, few empirical studies have investigated the likely evolutionary impacts. Here, we used DNA recovered from a temporal series of archived North Sea cod (Gadus morhua) otoliths, to investigate genetic diversity within the Flamborough Head population between 1954 and 1998, during which time the population underwent two successive declines. Microsatellite data indicated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

15
208
3

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 222 publications
(226 citation statements)
references
References 64 publications
15
208
3
Order By: Relevance
“…Comparison with other marine species For most marine species, the estimated N e /N ratio is between three to five orders of magnitude smaller than the census population size (Hauser et al, 2002;Planes and Lenfant, 2002;Turner et al, 2002;Hutchinson et al, 2003;Hoarau et al, 2005;Gomez-Uchida and Banks, 2006;Poulsen et al, 2006;Laurent and Planes, 2007;Ovenden et al, 2007). All these species are highly fecund species with a typical type III survival curve (that is, high fecundity and high juvenile mortality).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Comparison with other marine species For most marine species, the estimated N e /N ratio is between three to five orders of magnitude smaller than the census population size (Hauser et al, 2002;Planes and Lenfant, 2002;Turner et al, 2002;Hutchinson et al, 2003;Hoarau et al, 2005;Gomez-Uchida and Banks, 2006;Poulsen et al, 2006;Laurent and Planes, 2007;Ovenden et al, 2007). All these species are highly fecund species with a typical type III survival curve (that is, high fecundity and high juvenile mortality).…”
Section: Discussionmentioning
confidence: 99%
“…This kind of variance seems high for a species with low fecundity and high juvenile survival. In comparison with marine species expected to have a high variance in reproductive success (high fecundity and low juvenile survival), the variance is between 57 000 and 1 000 000 for the North Sea plaice (Pleuronectes platessa), between 18 000 and 165 000 for the New Zealand red snapper (Pagrus auratus) (Hauser et al, 2002), between 30 000 and 240 000 for the North Sea cod Effective population size in thornback ray M Chevolot et al (Gadus morhua) (Hutchinson et al, 2003) and 4500 for the red drum (S. ocellatus; Turner et al, 2002). The estimated variance in reproductive success for thornback ray is, therefore, in the same range as these species.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Humans are extremely effective predators, often exerting higher mortality on animal populations than natural predators (Darimont, Fox, Bryan, & Reimchen, 2015), with potential evolutionary effects on wild populations (Haldane, 1942; Hutchinson, van Oosterhout, Rogers, & Carvalho, 2003; Jachmann, Berry, & Imae, 1995; Macnair, 1987; Voipio, 1950). Of particular concern in this context are fish populations, as they are under very high levels of exploitation with life histories that typically involve group living (Jørgensen et al., 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Information on genetic diversity of wild populations is also an essential component in the start of any breeding program for developing domesticated stocks for farm culture (Fjalestad et al 1993;Gjøen and Bentsen 1997;Hena et al 2005;Rezk et al 2003). It has been shown that overexploitation in fisheries can induce a rapid loss of genetic variation of target species, which may diminish the adaptability and persistence of the species (Hauser et al 2002;Hutchinson et al 2003;Smith et al 1991;Turner et al 2002). A lack of a policy regarding farming industries can result in introgression of non-native or domesticated genes into wild populations, potentially causing a loss in genetic variability (Bekkevold et al 2006;Fleming et al 2000;Hindar et al 2006;McGinnity et al 2003).…”
Section: Introductionmentioning
confidence: 99%